Analisa Kerjasama Pihak Corporate dengan Masyarakat dalam Pengembangan Pariwisata di Desa Singapadu Kaler, Kabupaten Gianyar - Claudia Grace Kusumawardani; Putri Kusuma Sanjiwani (JURNAL DESTINASI PARIWISATA, 2020)
In village tourism developing, it is necessary to have cooperation carried out by tourism Stakeholders, both Government, Community and Entrepreneurs or private parties. The collaboration must be balanced according to the status and role of each stakeholder so that harmonious cooperation can be created that is impartial to anyone. The research method used is a qualitative method with qualitative data analysis techniques, The source of data from this study comes from primary and secondary data. Data collection techniques are carried out by observation, in-depth interviews and documentation. Determination of informants is done by purposive sampling procedure. The results of this study indicate that based on the characteristics, tasks, objectives and functions of the BUMDES ( Badan Usaha Milik Desa ) are still not optimal, it can be seen that a number of things that have not yet fulfilled and still need to be reviewed so that BUMDES ( Badan Usaha Milik Desa) can collaborate and coordinate tourism village units optimally. Keywords: Corporate, Community, Tourism Development